Strengthening Social Morality through the Qur'anic Discourse on LGBT: A Comparative Exegetical Study of Tafsir al-Qur'an li al-Shabab and Tafsir Marah Labid - Rohmat, Nur; Mufid, Abdul; Arif, Mohammad; Mahmudi, Ahmad (Universitas Muhammadiyah Surakarta, 2025)
LGBT is a sexual orientation that does not represent the tendency of the majority of people, but rather a phenomenon that appears outside the general pattern of sexual orientation. The phenomenon will be viewed from the perspective of the Qur'an, the holy book of Muslims. This research uses the method of tafsir maudhu'i al-Farmawi by looking at the interpretation of female scholars, Fātin al-Falakī